1996
DOI: 10.1063/1.361513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of V/III ratio on ordering in GaInP: Atomic scale mechanisms

Abstract: Ga 0.5 In 0.5 P layers have been grown by organometallic vapor-phase epitaxy using various values of input V/III ratio for two phosphorus precursors, phosphine, the conventional precursor, and tertiarybutylphosphine ͑TBP͒, a newly developed, less-hazardous precursor. For growth on nominally ͑001͒ GaAs substrates misoriented by 3°͑and in some cases by 0°or 6°͒ to produce ͓110͔ steps on the surface at a growth temperature of 620°C, the Cu-Pt-type ordering is found to be strongly affected by the input flow rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…[8][9][10] Thus, in principle, a much more attractive approach would be to change the flow rate of the phosphorus precursor to produce the desired change in order parameter, although the changes in bandgap energy are typically considerably smaller than for changes in temperature. The initial attempts to produce heterostructures in this way used PH 3 as the P precursor at a growth temperature of 620°C.…”
Section: Growth Of Order/disorder Heterostructures In Gainp Using a Vmentioning
confidence: 98%
See 2 more Smart Citations
“…[8][9][10] Thus, in principle, a much more attractive approach would be to change the flow rate of the phosphorus precursor to produce the desired change in order parameter, although the changes in bandgap energy are typically considerably smaller than for changes in temperature. The initial attempts to produce heterostructures in this way used PH 3 as the P precursor at a growth temperature of 620°C.…”
Section: Growth Of Order/disorder Heterostructures In Gainp Using a Vmentioning
confidence: 98%
“…6 This has been demonstrated by the recent experimental observation, using surface photo absorption (SPA), that the concentration of 110 [ ] P-dimers on the (001) surface correlates closely with the degree of order (S) produced during OMVPE growth as the growth temperature and partial pressure of the P precursor (P P ) are varied. [7][8][9][10] It has been suggested that the step structure on the surface during growth may also play a role in the ordering process. [10][11][12] (Received March 13, 1997; accepted May 6, 1997)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of the energy bandgap of a CuPt ordered semiconductor alloy depends on its atomic ordering degree, Z. The CuPt atomic ordering degree of a III-V semiconductor epitaxy grown layer has been found changing with the growth conditions, such as the substrate temperature during the growth [7], material growth rate [8], input V/III flux ratio [9] surfactants [10], etc., in the MOVPE growths.…”
Section: Introductionmentioning
confidence: 99%
“…The use of variations in V/III ratio to grow heterostructures has a technical advantage over the use of growth temperature despite the fact that the degree of order can currently be controlled over a wider range with variation of growth temperature. [9][10][11] This advantage stems from the fact that changing the growth temperature requires an interruption of the growth for a period of several minutes 6,7 to allow the temperature to stabilize. This interruption could have a negative impact on the quality of the interface in the heterostructure.…”
Section: Introductionmentioning
confidence: 99%